Analysis Of The Influence Of Islamic Marketing Ethics On Customer Satisfaction At Padang Padang Restaurant Morning Afternoon - Ilham Arydani; Mohammad Bintang Pamuncak (SEAN Institute, 2024)
This study aims to determine the application of Islamic marketing ethics to customer satisfaction of RM Pagi Sore in the Bogor area. The sample in this study were consumers of RM Pagi Sore. The research method used is the descriptive quantitative method. The sample was taken from 70 respondents using the purposive sampling technique. Hypothesis testing using multiple linear regression analysis methods with SPSS version 22. The results of the analysis show that Islamic marketing ethics positively and significantly influence customer satisfaction. This finding highlights the importance of applying Islamic ethical principles in marketing strategies to increase customer satisfaction in the restaurant industry. The managerial implications emphasize the need for restaurants to strengthen values such as Al-Siddiq (true, honest), Al-Amanah (trusted, credible), Al-tabligh (communicative, transparent), Al-fathanah (intelligent, professional) towards the environment in every aspect of its operations to build sustainable customer trust and loyalty.